1995
DOI: 10.1021/jm00016a017
|View full text |Cite
|
Sign up to set email alerts
|

(1S,2S)-1-(4-Hydroxyphenyl)-2-(4-hydroxy-4-phenylpiperidino)-1-propanol: A Potent New Neuroprotectant Which Blocks N-Methyl-D-Aspartate Responses

Abstract: (1S,2S)-1-(4-Hydroxyphenyl)-2-(4-hydroxy-4-phenylpiperidino)-1-propanol (20, CP-101,606) has been identified as a potent and selective N-methyl-D-aspartate (NMDA) antagonist through a structure activity relation (SAR) program based on ifenprodil, a known antihypertensive agent with NMDA antagonist activity. Sites on the threo-ifenprodil skeleton explored in this report include the pendent methyl group (H, methyl, and ethyl nearly equipotent; propyl much weaker), the spacer group connecting the C-4 phenyl group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
1
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(122 citation statements)
references
References 9 publications
5
114
1
1
Order By: Relevance
“…This observation is consistent with a developmental increase of release sites and of receptor density at these sites. In contrast to our expectations following reports of high expression of the NR2B subunit in the developing cortex, haloperidol and CP101,606, specific blockers of receptors comprising NR1ÏNR2B subunits (Chenard et al 1995;Ilyin et al 1996), failed to antagonize mN_EPSCs in the majority of cells in the visual cortex at P13-P15. While CP101,606 never produced significant changes in the mean mN_EPSC amplitude, haloperidol produced significant alterations in a few of the neurons tested.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This observation is consistent with a developmental increase of release sites and of receptor density at these sites. In contrast to our expectations following reports of high expression of the NR2B subunit in the developing cortex, haloperidol and CP101,606, specific blockers of receptors comprising NR1ÏNR2B subunits (Chenard et al 1995;Ilyin et al 1996), failed to antagonize mN_EPSCs in the majority of cells in the visual cortex at P13-P15. While CP101,606 never produced significant changes in the mean mN_EPSC amplitude, haloperidol produced significant alterations in a few of the neurons tested.…”
Section: Discussioncontrasting
confidence: 99%
“…At the same time, recent studies have identified pharmacological agents which are able to antagonize in a selective manner NMDARs containing the NR1ÏNR2B subunits; these include ifenprodil (Williams, 1993), haloperidol (Ilyin, Wittermore, Guastella, Weber & Woodward, 1996) and the novel ifenprodil derivative, CP101,606 (Chenard et al 1995;Boeckman & Aizenman, 1996). Recently, antagonism of hippocampal NMDA-mediated synaptic currents by ifenprodil has been shown to be dependent on development (Kirson & Yaari, 1996), implying a developmental decrease in synaptic receptors comprising the NR2B subunit.…”
mentioning
confidence: 99%
“…Ketamine HCl (Hospira; Lake Forest, IL) and CP-101,606, ((1S,2S)-1-(4-hydroxyphenyl)-2-(4-hydroxy-4-phenylpiperidino)-1-propanol) mesylate salt, synthesized as described (Chenard et al, 1995) and dissolved in saline. Doses for both compounds are expressed as free base.…”
Section: Compoundsmentioning
confidence: 99%
“…Although, like other un-competitive NMDAR antagonists they may have some adverse effect on learning and memory, it was proved that they have a wider separation between doses that are effective in seizure or stroke models and those that disrupt learning and memory. The limited information on the novel NR2B subunit selective antagonists (Table 1) such as CP-101,606 (traxoprodil) [33,98], Ro25-6981 [59], Co-101244 [225], CI-1041 [35] and RG-1103 [18] also suggests that these drugs are better tolerated and are largely devoid of adverse CNS effects at antinociceptive doses, at least with respect to psychotomimetic, ataxic and sedative effects [19,29,35,57,146,203].…”
Section: Nr2b Subunit Selective Nmdar Antagonistsmentioning
confidence: 99%